PENGARUH KESADARAN WAJIB PAJAK, SANKSI PAJAK, MOTIVASI MEMBAYAR PAJAK DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Pada Wajib Pajak Orang Pribadi UMKM di KPP Pratama Tampan Pekanbaru) - Resi Gusrefika; Zirman Zirman; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of taxpayer awareness, tax sanctions, tax motivation and level of education to taxpayer compliance. This research was conducted on Individual Tax Payer Of SMEs At Pratama Tampan Pekanbaru Tax Office. Population used in this research is all individual taxpayer of SMEs which registered at Pratama Tampan Pekanbaru Tax Office as much as 3.950 Taxpayer. The sample of this research is Individual Tax Payer of SMEs as much as 75 Taxpayers. Getting of data by using Simpel Random Sampling. Data analysis was done with multiple linear regression model with SPSS version 21.0 software. Result of the research was found that Taxpayer Awareness, Tax Sanctions and Tax Motivations have a direct influential on taxpayer compliance. But, Education Level has not direct influential on taxpayer compliance. From the results of the test F, found that the awareness of taxpayers, tax sanctions, tax motivation and education level simultaneously influential on taxpayer compliance with the value that > Ftabel is 7,835 > 2,46.Keywords : tax compliance, taxpayer awareness, tax sanctions, tax pay motivation and level of education